The impact of the package opening process on product returns - Wenyan Zhou; Oliver Hinz; Alexander Benlian (Business Research, 2018)
High product return rates are an increasingly pressing challenge for many e-retailers around the world. To address this problem, this paper offers a new perspective by focusing on the critical moment of the package-opening process. Going beyond previous research, which has primarily focused on website information and the product itself, we examine the effects of the outside appearance (i.e., the color of the delivery package) and contents of the delivery package (i.e., extra gifts, coupons, and preprinted return labels) on consumer return behavior. Our findings across two experimental studies and an observational field study show that a well-considered package design, including colorful packaging and extra gifts, significantly lowers consumers' return intentions and actual returns. We also explore the process of consumers' cognitive-affective reactions after opening a delivery package. During this two-stage reaction process, pleasure plays a crucial role in the consumer's return choice.
Keywords: 650; Online purchase; Consumer return behavior; Color; Delivery packages; Free gifts